Effect of 3-aminobenzamide on perforation an experimental colitis model - Menekse, Ebru; Aydın, Sezai; Sepici Dinçel, Aylin; Eroğlu, Abdullah; Dolapçı, Mete; Yıldırım, Osman; Cengiz, Ömer (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: The anti-inflammatory activity of 3-aminobenzamide (3-AB) has been shown via histopathology and immunohistochemistry in various colitis models. We aimed to study the effects of 3-AB on tissue mechanical endurance and, associatively, preventing perforation in colitis. Materials and Methods: Thirty male Wistar albino rats were randomly divided into three groups. Rectal saline was administered to Group 1 (sham + saline). Rectal trinitrobenzensulphonic acid was applied to induce colitis in Group 2 (colitis + saline) and Group 3 (colitis + 3-AB). Groups 1 and 2 were treated intraperitoneally with saline (1 ml every 12 hours) and Group 3 was treated with 3-AB (10 mg/kg every 12 hours). After seven days, rats were sacrificed and colon lipid peroxidation levels, the serum tumor necrosis factor alpha (TNF-α) level, bowel bursting pressures, and bowel wall tensions were measured. Results: Bowel bursting pressure in Group 2 was significantly lower than in Groups 1 and 3 (p<0.001 for both groups). Bowel wall tension in Group 2 was significantly lower than in Groups 1 and 3 (p<0.001 for both groups). There were no significant differences between groups for serum TNF-α levels. For lipid peroxidation, malondialdehyde (MDA) levels were increased in Groups 2 and 3 compared to Group 1. Conclusion: 3-AB may aid prevention of perforations that develop in inflammatory bowel disease, requiring surgical treatment.